Balancing values and obligations when obtaining informed consent: Healthcare professionals' experiences in Swedish paediatric oncology. (16th October 2019) - Schröder Håkansson, Anna; Pergert, Pernilla; Abrahamsson, Jonas; Stenmarker, Margaretha
Abstract: Aim: To explore Swedish healthcare professionals' (HCPs) clinical experiences of the informed consent process (ICP) and to compare experiences between the professions. Methods: In this nationwide study six paediatric oncologists (POs) and eight research nurses (ReNs) from all Swedish paediatric oncology centres were interviewed. The material was analysed using Grounded theory, a qualitative constant comparative method. Results: The participants' main concern was how to fulfil research obligations without putting too much strain on a family in acute crisis, which led to the core category of balancing values and obligations of both healthcare and research. To handle the challenges the participants' struggled to safeguard the families from psychological harm, tried to adjust to the families, and gradually introduced research while building trust. The conceptual model developed in the study highlights potential consequences of this balancing act with a risk of diminishing the family's autonomy through HCPs acting authoritatively (in particular POs) or with overprotection (in particular ReNs). Conclusion: Paediatric oncology is a research integrated healthcare environment. The HCPs need personal, professional and institutional support regarding ICP‐related ethical issues, decisions and implications in this intertwined context. Furthermore, HCPs need to be aware of the potential long‐term risk of developing professional moral distress.